Nanotechnology Toolkit for Combating COVID‐19 and Beyond. Issue 4 (10th March 2022) - Muthiah, Giredhar; Sarkar, Ankita; Roy, Shounak; Singh, Prem; Kumar, Praveen; Bhardwaj, Keshav; Jaiswal, Amit
Abstract: The outbreak of SARS‐CoV‐2 is unlikely to be contained anytime soon with conventional medical technology. This beckons an urgent demand for novel and innovative interventions in clinical protocols, diagnostics, and therapeutics; to manage the current "disease X" and to be poised to counter its successor of like nature if one were to ever arise. To meet such a demand requires more attention to research on the viral‐host interactions and on developing expeditious solutions, the kinds of which seem to spring from promising domains such as nanotechnology. Inducing activity at scales comparable to the viruses themselves, nanotechnology‐based preventive measures, diagnostic tools and therapeutics for COVID‐19 have been rapidly growing during the pandemic. This review covers the recent and promising nanomedicine‐based solutions relating to COVID‐19 and how some of these are possibly applicable to a wider range of viruses and pathogens. We also discuss the type, composition, and utility of nanostructures which play various roles specifically under prevention, diagnosis, and therapy. Further, we have highlighted the adoption and commercialization of some the solutions by large and small corporations alike, as well as providing herewith an exhaustive list on nanovaccines. Abstract : Herein, we provide a comprehensive review about nanomaterial‐based technologies for diagnosis and prevention of SARS‐Cov‐2. We also review the applicability of nanomaterial in vaccine development and how nanomaterials can be used as a therapeutic agent to inhibit infection and destroy coronaviruses.